Stabilities of infant behaviors and maternal responses to them - Bornstein, Marc H. (2020)
Consistency in the order of individuals in a group across substantial lengths of time-stability-is a central concept in developmental science for several reasons. Stability underscores the meaningfulness of individual differences in psychological phenomena; stability informs about the origins, nature, and overall developmental course of psychological phenomena; stability signals individual status and so affects the environment, experience, and development; stability has both theoretical and clinical implications for individual functioning; and stability helps to establish that a measure constitutes a consequential individual-differences metric. In this three-wave prospective longitudinal study (Ns = 40 infants and mothers), we examined stabilities of individual variation in multiple infant behaviors and maternal responses to them across infant ages 10, 14, and 21 months. Medium to large effect size stabilities in infant behaviors and maternal responses emerged, but both betray substantial amounts of unshared variance. Documenting the ontogenetic trajectories of infant behaviors and maternal responses helps to elucidate the nature and structure of early human development.